Pediatric airway surgery management of laryngotracheal stenosis in infants and children - Monnier, Philippe; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book provides detailed insight into the difficult problem of pediatric airway management. Each chapter focuses on a particular condition in a very practical manner, describing diagnostic procedures and precisely explaining surgical options with the help of high-quality illustrations. Both established treatment modalities and new management concepts are considered in depth, and controversies relating to the most difficult airway reconstructions are discussed. To help the reader, boxes are included to summarize procedures and to list tips, tricks, and traps relevant to daily practice.
The compromised pediatric airway: challenges facing families and physicians -- Applied surgical anatomy of the larynx and trachea -- Clinical evaluation of airway obstruction -- Equipment and instrumentation for diagnostic and therapeutic endoscopy -- Endoscopic assessment of the compromised pediatric airway -- Laryngomalacia (LM) -- Vocal cord paralysis (VCP) -- Congenital subglottic stenosis (C-SGS) -- Laryngeal web and atresia -- Subglottic haemangioma (SGH) -- Ductal cysts, saccular cysts and laryngoceles -- Laryngeal and tracheal clefts -- Congenital tracheal anomalies -- Acquired post-intubation and tracheostomy-related stenoses -- External laryngeal trauma -- Neoplastic lesions of the larynx and trachea -- Preoperative assessment, indications for surgery and parental counseling -- Endoscopic techniques for laryngotracheal stenosis -- Laryngotracheoplasty and laryngotracheal reconstruction -- Partial cricotracheal resection -- Tracheotomy -- Tracheal resection and anastomosis -- Revision surgery.
Electronic reproduction.
Keywords: Trachea -- Surgery; Children -- Surgery; Electronic books